Effectiveness of Environmental Law Enforcement against Industrial Waste Pollution: Problems of Supervision, Compliance, and Sanction Implementation - Imam Taufik Harahap; Dian Eriani; Syah Iskandar; Mailina Harahap; Ismatur Rahmi (Britain International for Academic Research (BIAR) Publisher, 2026)
Industrial waste pollution remains a significant environmental problem requiring effective law enforcement to ensure sustainable environmental protection and management. This study aims to analyze the effectiveness of environmental law enforcement on industrial waste pollution, emphasizing the aspects of supervision, compliance of industrial actors, and the application of sanctions. The study uses a normative legal research method with a statute approach, a conceptual approach, and a case approach. Primary legal materials include Law Number 32 of 2009, Law Number 6 of 2023, Government Regulation Number 22 of 2021, and relevant court decisions, supported by secondary legal materials in the form of books, scientific journals, and official documents. The results of the study indicate that the effectiveness of law enforcement is not optimal despite an adequate regulatory framework. The main obstacles lie in inconsistent supervision, varying levels of compliance among industrial actors, and the application of sanctions that have not fully provided a deterrent effect. Therefore, strengthening supervisory capacity, enhancing a culture of compliance, and consistent enforcement of sanctions are important prerequisites for realizing an effective, equitable, and sustainable environmental law enforcement system.